Writing Structure of Disaster Management Planning Document in West Java - Kurniasih, Dewi; Kalalangi, Rita; Prihandini, Asih (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
West Java Province is one of the provinces that have a tendency of high level of disaster in Indonesia. This requires serious attention from the government that must be incorporated into disaster management planning document in West Java. The research problem lies in the writing structure of the document. Qualitative approach with content analysis is used as the method. Documentation and interview studies are performed as the data collection technique. The research’s’ results show that the contents of disaster management planning documents in West Java has covered zones, strategies, focus, targets, priorities and activities arranged in sequence according to the format determined by the government in integrative manner. Our recommendation is that the disaster management in West Java still requires coordination and cooperation of several related parties.